Tinjauan Sistem Distribusi Mushaf Al-Qur’an Kementerian Agama di Jawa Timur - Jaeni, Ahmad (SUHUF, 2014)
This article reviews the distribution system of Qur’an carried out by Ministry of Religious Affairs in East Java. Based on the research results, the distribution of Qur’an adopts multi-channel distribution system, a system that enables every channel of the distribution plays two functions, as intermediary and retailer. Although quite effectively accelerate the distribution process, but this system opens the possibility of overlapping target distribution. As a result, the distribution is uneven and not well targeted. Thus, segmenting the target of the distribution in any distribution channel into an offer solutions. Keywords: distribution system, Qur’an, Ministry of Religious Affairs